Pengaruh Lifestyle, Brand Equity Dan Social Media Marketing Terhadap Keputusan Pembelian Pakaian Bekas Yang Tersebar Di Kecamatan Lowokwaru Kota Malang - Murtadho, Naufal Alit; Asiyah, Siti; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was also applied to analyze the influence of Lifestyle, Brand Equity and Social Media Marketing on purchasing decisions for used clothing spread across Lowokwaru Village, Malang City. This research uses quantitative techniques. The population is students in Malang City. The information collection model uses a questionnaire distribution procedure. The sample in this finding used purposive sampling with the Lemeshow formula, totaling 100 respondents among students in Malang City. The variables in this research are Lifestyle (X1), Brand Equity (X2), Social Media Marketing (X3) and Purchase Decisions (Y). The analysis methods used include instrument testing (validity test and reliability test), normality test, classical assumption test, multiple linear regression analysis test, hypothesis test, and coefficient of determination test with the help of SPSS. Several things were found, namely 1. Simultaneously or together, Lifestyle items (X1), Brand Equity (X2) and Social Media Marketing (X3) had a positive and significant influence on Purchasing Decisions (Y). 2. Lifestyle items (X1) have a positive and significant influence on purchasing decisions (Y). 3. Brand Equity Items (X2) have a positive and significant influence on Purchasing Decisions (Y). 4. Social Media Marketing items (X3) have a positive and significant effect on Purchasing Decisions (Y). Keywords: Lifestyle, Brand Equity, Social Media Marketing and Purchase Decision